Industry, flexibility, and demand response: Applying German energy transition lessons in Chile. (August 2019) - Valdes, Javier; Poque González, Axel Bastián; Ramirez Camargo, Luis; Valin Fenández, Meylí; Masip Macia, Yunesky; Dorner, Wolfgang
Abstract: Demand side management (DSM) contributes, among its other purposes, to provide stability and flexibility to energy systems that include a high proportion of variable renewable energy in pioneer countries and those which recently began their energy transition. Among DSM policies, implementation of measures and mechanisms for a demand response (DR) is not a trivial matter. This study presents a review and comparative analysis of the major energy policy developments in Germany and Chile. Based on i) the relevance of the industry sector in both countries, ii) the difficulty in implementing the regulatory framework and iii) the importance given to the industrial customers in the German legislation and DR literature, the following analysis will focus on both medium and large industrial customers. The goals are to review the challenges in untying the full DR potential of the productive industry and to provide recommendations for the promotion of DR in Chile. Emphasis is placed on the lessons learned in fitting the wide potential of DR in the German electricity markets. A review of the successes and failures of the German experience reveals the potential risk that poor policy implementation can have in both the short and long term.